A triphenylamine-based polymer with anthraquinone side chain as cathode material in lithium ion batteries. (1st September 2018) - Huang, Wanrong; Jia, Tao; Zhou, Guangying; Chen, Sha; Hou, Qiong; Wang, Yuhai; Luo, Suilian; Shi, Guang; Xu, Bingjia
Abstract: A triphenylamine-based polymer poly[ N -(anthraquinone-2-yl)- N, N -diphenylamine] (PDPA-AQ) with anthraquinone side chain was synthesized by a simple chemical oxidative polymerization. Due to the introduction of anthraquinone units with a high specific capacity in the side chain, the polymer PDPA-AQ has a high theoretical specific capacity, about twice of polytriphenylamine (PTPA). The lithium ion batteries based on PDPA-AQ as cathode active material and lithium foil as anode were assembled and their electrochemical properties were investigated. For a comparison, the electrochemical performance of the monomer DPA-AQ was also studied. Both monomer DPA-AQ and polymer PDPA-AQ have high initial discharge specific capacity, about 129 mAh g −1 and 159 mAh g −1 respectively, which are higher than the theoretical specific capacity of PTPA-based cells. The polymer PDPA-AQ has better discharge specific capacity, cycle performance and rate performance than monomer DPA-AQ, which shows that the design idea of introducing an electrochemically active carbonyl compound into the polytriphenylamine side chain can improve the specific capacity of the PTPA.